Isolation, Identification, and Antibacterial Properties of Prodigiosin, a Bioactive Product Produced by a New Serratia marcescens JSSCPM1 Strain: Exploring the Biosynthetic Gene Clusters of Serratia Species for Biological Applications - Rajaguru Arivuselvam; Ayed A. Dera; Syed Parween Ali; Yasser Alraey; Ahmed Saif; Umme Hani; Sivaa Arumugam Ramakrishnan; Mohamed Sheik Tharik Abdul Azeeze; Raman Rajeshkumar; Aishwarya Susil; Haritha Harindranath; B. R. Prashantha Kumar (MDPI AG, 2023)
Prodigiosin pigment has high medicinal value, so exploring this compound is a top priority. This report presents a prodigiosin bioactive compound isolated from Serratia marcescens JSSCPM1, a new strain. The purification process of this compound involves the application of different chromatographic methods, including UV-visible spectroscopy, high-performance liquid chromatography (HPLC), and liquid chromatography-mass spectrometry (LC/MS). Subsequent analysis was performed using nuclear magnetic resonance (NMR) to achieve a deeper understanding of the compound's structure. Finally, through a comprehensive review of the existing literature, the structural composition of the isolated bioactive compound was found to correspond to that of the well-known compound prodigiosin. The isolated prodigiosin compound was screened for antibacterial activity against both Gram-positive and Gram-negative bacteria. The compound inhibited the growth of Gram-negative bacterial strains compared with Gram-positive bacterial strains. It showed a maximum minimum inhibitory concentration against Escherichia coli NCIM 2065 at a 15.9 ± 0.31 μg/mL concentration. The potential binding capabilities between prodigiosin and the OmpF porin proteins (4GCS, 4GCP, and 4GCQ) were determined using in silico studies, which are generally the primary targets of different antibiotics. Comparative molecular docking analysis indicated that prodigiosin exhibits a good binding affinity toward these selected drug targets.